PANDANGAN ANGGOTA KORPS HMI-WATI SURABAYA TENTANG PEREMPUAN BERDAYA - Desia Adilia Nur Cahyani; Maya Mustika Kartika Sari (Universitas Negeri Surabaya (Unesa), 2021)
The purpose of this study is to express the views of members of the Kohati Surabaya about empowered women. This research is examined using Nancy Hartsock's Standard theory. The main concept of standpoint theory includes a perspective, situated knowledge and the sexual division of labor. This study uses a qualitative research approach with an exploratory descriptive design. The data collection techniques used were in-depth interviews and documentation. The research informants were determined using purposive sampling technique. The number of informants in this study were three people consisting of the General Secretary of the Surabaya Branch of the Kohati, members of the Department of Education and Training, and Deputy General Secretary for Inter-Institutional Relations. The results showed that women in the view of members of the Kohati Surabaya were influenced by the literacy process and the interpretation of values ​​from a gender perspective, a religious perspective, and a sociocultural perspective. In the view of members of the Surabaya branch of Kohati, empowered women are women who can do the expected aspects such as gender literacy but do not conflict with religion. That empowered women are they have the same opportunity to access productive resources, participate in exploiting their potential, have power / control over their survival, and have the same opportunity to enjoy the results of resource utilization / development. The results of this study confirm the standpoint theory put forward by Nancy Hartsock that views are formed from experiences that are structured by one's position in the social hierarchy, namely the emphasis on women's autonomy in various aspects of life. Keywords: Kohati, Woman, Empower